2018
DOI: 10.1140/epjb/e2018-90055-3
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of longitudinal phonons with discrete breather in strained graphene

Abstract: We numerically analyze the interaction of small-amplitude phonon waves with standing gap discrete breather (DB) in strained graphene. To make the system support gap DB, strain is applied to create a gap in the phonon spectrum. We only focus on the in-plane phonons and DB, so the issue is investigated under a quasi-one-dimensional setup. It is found that, for the longitudinal sound waves having frequencies below 6 THz, DB is transparent and thus no radiation of energy from DB takes place; whereas for those soun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…To make these results more quantitative we use the energy density in Eq. ( 21) to define initial, reflected and transmitted energies as [18]…”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To make these results more quantitative we use the energy density in Eq. ( 21) to define initial, reflected and transmitted energies as [18]…”
Section: Numerical Resultsmentioning
confidence: 99%
“…For future investigations, it would be particularly interesting to consider the scattering of large amplitude waves from a symmetric or asymmetric soliton. Several new interesting phenomena, such as soliton acceleration, the creation of multiple soliton and anti-soliton pairs, and resonant energy pumping, could eventually be observed [18,30]. where ∆ 2 ϕ n = 1 h 2 (ϕ n−1 − 2ϕ n + ϕ n+1 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Fourier law of thermal conductivity states that for macroscopic bodies, the heat flux is proportional to the temperature gradient with a proportionality coefficient κ, referred to as thermal conductivity. In a number of theoretical works [19][20][21][22][23][24][25][26][27][28][29][30][31], it was shown that in one-dimensional structures, Fourier's law does not work, in the sense that κ depends not only on the material, but also on the dimensions of the conductor, in particular, on its length L according to the power law κ ∼ L α , where the exponent is in the range 0 ≤ α ≤ 1. The case α = 1 corresponds to ballistic thermal conductivity, and for α = 0 we have normal, diffusive thermal conductivity obeying the Fourier law.…”
Section: Introductionmentioning
confidence: 99%
“…Hamiltonian many-body systems with nonlinear interactions admit quite generally a special class of periodic orbits, whose amplitude-dependent frequency does not resonate by construction with any of the linear (normal) modes (NM) and whose oscillation pattern is typically exponentially localized in space. These modes, termed discrete breathers (DB) 1-3 or intrinsic localized modes (ILM), 4 have been shown theoretically to exist at zero temperature in a wide range of systems, including model lattices of beads and springs, such as the celebrated Fermi-Pasta-Ulam (FPU) chain, 5 real 2D and 3D crystals, 6 both in the gap 7 and above the phonon spectrum, 8 including cuprate high T c superconductors, 9 boron nitride, 10 graphene [11][12][13] and diamond, 14 disordered media [15][16][17] and biomolecules, 18 including proteins. 19,20 Nonlinear modes of this kind are surmised to play a subtle role in many condensed-matter systems.…”
Section: Introductionmentioning
confidence: 99%